Convergence Islamic Values as Economic Development - Dede Aji Mardani (Jambura Equilibrium Journal, 2021)
Tasikmalaya economic growth has been increasing economic growth in the last 10 years .This is influenced by the fulfillment of unlimited human needs.This study aims to analyze the relationship between religious values held by entrepreneurs and economic growth. The method used is descriptive qualitative with an economic anthropology approach. The results show that entrepreneurs who come from various ethnic in Indonesia show that religious teachings really influence the level of their business activities. That business is not only for material purposes only but is further than that as an end day investment. The values of religious sacredness have been inherent in the personality of entrepreneurs such as honesty, frugality, openness and transparency, which are religious values taught when making transactions. These religious values in fact have an impact on increasing the value of sales in their business, with the increase in their business directly driving regional economic growth. income increases, unemployment decreases, local taxes increase. This shows that the work ethic of Muslim entrepreneurs in Tasikmalaya has helped in national economic growth. Finally, the local government can maintain harmony and peace in the economic and political situation of Tasikmalaya so that the climate of economic growth and the prosperity of the people can be maintained. Keywords: Islamic Work Ethic; Islamic Values; Moslem Entrepreneur